A 3-layer RDH method in encrypted domain for medical information security. (15th November 2019) - Mondal, Jayanta; Swain, Debabala
Digitisation of sensitive images demands a lossless security mechanism and a sophisticated privacy preservation technique. Sensitive imagery, e.g., medical, forensic, military images, etc., needs special care during transmission as a little distortion can lead to catastrophic diagnosis mistake. With immense advancements, popularity, and success of service-oriented architecture (SOA), providing safe and secure online medical facility is one hard challenge for both research community and the industry. This paper proposes a 3-layer embedding mechanism enabled reversible data hiding (RDH) scheme with additional electronic patient record (EPR) hiding technique for encrypted medical images. LSB modification and LSB substitution technique are used for the embedding and EPR hiding. The experiments carried out on the medical test images on three levels of embedding and the experimental results show great potential in terms of security, embedding capacity, and recovered image quality.